Optimizing membrane performance using various filler materials in membrane fabrication for enhancing gas separation efficiency: a review - Roslin, Putri Nadhirah; Kamaruzaman, Sazlinda Binti; Johari, Ili Syazana; Yahaya, Noorfatimah (College of Graduate Studies, Walailak University, 2024)
The membrane technology has been receiving significant interest in both research and industrial applications, particularly in the separation of CO2/CH4. These methods, as published, aim to overcome the limitations of pure polymeric membranes and offer an alternative approach in separation techniques where membrane technology can overcome the constraints of conventional methods such as Solid Phase Extraction (SPE) and Liquid-Liquid Extraction (LLE). Fabricating membranes using fillers as adsorbents can enhance membrane separation performance due to their porous nature. Hence, the selection of suitable fillers is crucial to maximize membrane efficiency in separating analytes. This paper will review 3 types of fillers-metal-organic frameworks, carbonaceous nanomaterials and mesoporous molecular sieves-from various research papers published in recent years